Community Pharmacy Marketing: Strategies for Success - Jennifer L. Rodis, Pharm.D., B.C.P.S; Bella H. Mehta, Pharm.D; Kristina D. Wood, Pharm.D; Megan Offenberger, Pharm.D (University of Minnesota Libraries Publishing, 2011)
Purpose: As community pharmacies are implementing increasingly more clinical services they are faced with a new challenge of marketing these services. This article discusses The Ohio State University College of Pharmacy Clinical Partners Program's (Clinical Partners) experiences in marketing clinical services to patients, barriers encountered through these experiences, and presents suggestions for future marketing of services.Experience: Clinical Partners developed two targeted marketing projects and evaluated impact on patient enrollment in services. In January 2008, the pharmacy ran a series of radio advertisements, newspaper print advertisements, and face to face marketing in the community with the focus of each being patient care services. During this project five individuals expressed interest in Clinical Partners' services. Four indicated that they heard about Clinical Partners through the radio ad and one through the pharmacy website, though none chose to enroll in services. In 2009 Clinical Partners focused on marketing MTM in the form of a comprehensive medication review to current patients already enrolled in its anticoagulation management service. Following a three month period, 6 patients (8%) of the 71 patients receiving the marketing intervention chose to enroll in MTM. Four additional patients have enrolled in MTM since conclusion of the project.Discussion: These projects and a review of available literature revealed barriers that pharmacies encounter when marketing clinical services to patients in an outpatient setting including patients' unawareness of the role a pharmacist can play outside dispensing medications, patients' belief they do not need clinical services, and patients' unwillingness to pay a pharmacist out of pocket for services.Future Implications: To overcome these identified challenges, community pharmacies should consider integration of marketing techniques such as tailoring marketing to a target population, forming and utilizing relationships with patients, and looking to past marketing successes in developing marketing plans. Pharmacists should also be adventurous in exploring new ways to promote pharmacy clinical services to find creative solutions to barriers encountered. As community pharmacies continue to grow the realm of clinical services offered to patients, it is important also to develop and implement marketing strategies to support the services and expansion of the profession so that these services can be embraced by patients and the health care community.